Elephant Intrusion Warning System Using IoT and 6LoWPAN - Theerthagiri, Prasanna V.; Thangavelu, Menakadevi (International Journal of Sensors Wireless Communications and Control, 2020)
Background: This work proposes an automatic IoT based elephant intrusion warning system specifically designed for detecting elephant intrusions into Krishnagiri villages that border wildlife reserves and alerting threatened communities of the location. Objective: The first one is to find the spectral energy magnitude of the elephant's vocal communication signal and the other to determine highest pitch frequency produced by elephants. Methods: Sensors are used to identify the elephant intrusion through IoT based system. Result: This work designs an automatic IoT based elephant intrusion warning system maintainable by personnel without technical knowledge. Conclusion: The ultrasonic sensor detects the elephant’s movements and alerts the distance from the sensor to the elephant and location of the intrusion. The PIR sensor detects the elephant’s intrusion in the wildlife fences and informs to the forest officials and people.
Keywords: PIR sensor